"El apremio personal y la obligación del padre o madre y su incidencia en los derechos constitucionales de la niñez y adolescencia" - Moreno Franco, Silvia Eugenia (2014)
The present investigation arises from the problem that exists with food debtors and the lawsuit against them by not having or not wanting to settle the debt, so the judge ordered the suit for collection against the defendant, and damage leading to the payer and the payee. For this reason, in this research, has made the investigation and processing of information, literature, and legal doctrine. Thus, this legal research is structured into six chapters it. In the first chapter, the main part for understanding the problem and the effect was treated, it was necessary to hypothesize that the solution to the problem was in compliance with the research hypothesis. The second chapter refers to the theoretical framework, aspects: historical, doctrinal and legal. In the third chapter the methodology used in the research in question is described, the methods used, types of research, population, sample techniques and instruments used in data collection. In the fourth chapter the hypothesis is tested through the research results obtained by interviewing authorities located Quevedo, plus surveys of lawyers in free practice, you know as they are violated without any regard to the rights of obligors by those who are responsible to pay alimony. The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter discusses the proposal, objectives, description of the proposal, beneficiaries and social impact, etc